2008
DOI: 10.1159/000163040
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Subdural Effusion Secondary to Decompressive Craniectomy Performed in Patients with Severe Traumatic Brain Injury: Incidence, Clinical Presentations, Treatment and Outcome

Abstract: Objective: This study was performed to better understandpostoperative contralateral subdural effusion, an uncommon but serious complication secondary to decompressive craniectomy in patients with head trauma. Subjects and Methods: Data from medical records of 169 patients who underwent decompressive craniectomy after head trauma between 2003 and 2006 were collected. The data included demographics, clinical presentations, treatment and outcome. Results: Of the 169 patients, 11 (6.5%) had contralateral subdural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…Supporting this notion are the reported cases of SDGs contralateral to the side of the DC. 66,75,76 In our series of 39 cases with SDGs, 3 hygromas were contralateral to the side of DC (Fig. 2).…”
Section: Incidence Of Sdgsmentioning
confidence: 61%
See 2 more Smart Citations
“…Supporting this notion are the reported cases of SDGs contralateral to the side of the DC. 66,75,76 In our series of 39 cases with SDGs, 3 hygromas were contralateral to the side of DC (Fig. 2).…”
Section: Incidence Of Sdgsmentioning
confidence: 61%
“…The incidence of an SDG following DC for severe head injury is not well documented in the literature. [1][2][3]34,66,76,77 In a 2009 study Yang et al 75 demonstrated 11 cases (6.5%) of contralateral SDGs among 169 patients who had undergone DC for severe head injury. In an earlier study 76 these same authors documented 23 cases (21.3%) of SDGs in 108 patients who had undergone DC for severe head injury.…”
Section: Incidence Of Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contralateral SDG were constantly reported, the aetiology was thought to combine with external cerebral herniation. This outward herniation combined with rapid reduction in ICP may incite a pressure gradient between the two hemispheres and lead to the enlargement of the contralateral subdural space and the accumulation of effusion, especially when, initially, there is a possible rupture in the arachnoid layer after head trauma [12][13][14]. In this case, SDG harbored in the opposite side of midline shift besides the cranial defect has never been reported before.…”
Section: Discussionmentioning
confidence: 62%
“…2%-29%. 13,36,39,42 Subdual collection is the most common complication (50%) but it was seen in all of our patients.1,12,41 However none of them were symptomatic needing additional treatment. Seizure and congnitive dysfuntions occur due to the primary brain injury and is not related to the procedure.…”
Section: Discussionmentioning
confidence: 67%